On the direct formation of HO2 radicals after 248 nm irradiation of benzene C6H6 in the presence of O2 - Aluculesei, A.; Tomas, A.; Schoemaecker, C.; Fittschen, C. (Applied physics. B, Lasers and optics, 2008)
We present in this work the direct observation of HO 2 radicals after irradiation of benzene C 6 H 6 at 248 nm in the presence of O 2 . HO 2 radicals have been unambiguously identified using the very selective and sensitive detection of continuous wave cavity ring-down spectroscopy (cw-CRDS) coupled to a laser photolysis reactor. HO 2 radicals were detected in the first vibrational overtone of the OH stretch at 6638.20 cm -1 , using a DFB diode laser. This reaction might be important because 248 nm photolysis of H 2 O 2 has often been used in the past for studying the OH • -initiated degradation of C 6 H 6 , often using a large excess of C 6 H 6 over H 2 O 2 . The possible importance of the title reaction with respect to these former laboratory studies has been quantified through comparison with HO 2 • signals obtained from 248 nm photolysis of H 2 O 2 : one obtains under our conditions (excess O 2 and total pressure of 6.6 kPa helium) from the 248 nm irradiation of identical initial concentrations [C 6 H 6 ]=[H 2 O 2 ] the following relative initial radical concentrations: [HO 2 • ]=(0.28±0.05)×[OH • ]. Experiments with various O 2 concentrations have revealed that the origin of the HO 2 radicals is not the reaction of H-atoms with O 2 , but must originate from the reaction of O 2 with excited C 6 H 6 * . The quantum yield of C 6 H 6 * formation has been deduced to ϕ=0.2±0.1.